The commitment and satisfaction among UiTM staffs at northern region (Perlis, Kedah and Penang) / Ju Soon Yew ...[et al.] - Ju, Soon Yew; Din, Mohd Salleh; Hussin, Zaliha; Onn, Maziah (Institute of Research Management & Innovation (IRMI), 2009)
This study was conducted in MARA University of Technology (UiTM) Northern Region (Perlis, Kedah and Penang) Malaysia in 2005. There were five objectives of the study (i) to examine the level of organizational commitment (i.e., affective commitment, continuance commitment and normative commitment) of UiTM staff; (ii) to examine the level of job satisfaction of UiTM staff; (iii) to examine the relationship between organizational commitment and job satisfaction of UiTM staff; (iv) to explore the relationship between demographic variables (gender, marital status, age and years of service) and organizational commitment of UiTM staff; and (v) to explore the relationship between demographic variables and job satisfaction of UiTM staff. Findings suggested that the level of organizational commitment of UiTM staff is moderately high and the level of job satisfaction of UiTM staff is high. Findings also suggested that when organizational commitment of UiTM staff are high, their job satisfaction tend to high as well as a moderate positive correlation is found between the organizational commitment and job satisfaction. For affective commitment, finding revealed that significant differences are found between gender and age on the affective commitment. Secondly, for continuance commitment, finding revealed that significant differences are not found between demographic variables on the continuance organization commitment. Thirdly for normative commitment, finding revealed that significant differences are found between years of service and normative commitment. Lastly for job satisfaction, finding reveals that significant differences are found between gender, age and years of service on the job satisfaction. This study could provide meaningful information to the top management to design intervention programs to improve organizational commitment and job satisfaction among the UiTM staff. However, since the above findings were from a case study of organizational commitment and job satisfaction of UiTM Perlis, Kedah and Penang staff hence one need to exercise caution in generalizing to the other institutions of higher education settings.